Pediatric Distal Forearm Fracture Epidemiology in Malmö, Sweden—Time Trends During Six Decades - Lempesis, Vasileios; Jerrhag, Daniel; Rosengren, Björn E.; Landin, Lennart; Tiderius, Carl Johan; Karlsson, Magnus K. (Journal of Wrist Surgery, 2019)
Background The distal forearm fracture is the most common fracture in children. To allocate health care resources and evaluate if prevention strategies have been successful, it is essential to monitor changes in the epidemiology of common fractures.Methods Our hospital serves a city in which year 2006 included 276,244 inhabitants (49,664 <17 years of age). Through the hospital archives, we identified fractures sustained by individuals younger than 16 years during 2005 and 2006 and compared these with previous collected and published data from the same area and hospital for the period 1950 to 1994. We used official population data to estimate period-specific fracture rates and age and gender standardized time trends. We report rates as number of fractures per 100,000 person-years and changes between periods as rate ratios (RR) with 95% confidence intervals (CIs).Results We identified 521 distal forearm fractures, corresponding to a crude fracture incidence of 564/100,000 person-years (boys 719; girls 401). Age-adjusted fracture incidence was 70% higher in boys than in girls (RR 1.7; 95% CI 1.3–2.3). The age- and gender-adjusted hand fracture incidence was 40% higher in 2005–2006 than in 1950/1955 (RR 1.4; 95% CI 1.2 to 1.8) but no higher than 1993–1994 (RR 1.1; 95% CI 0.9–1.3). Fracture etiology of 2005 to 2006 included sports injuries in 41% and traffic accidents in 11% of the cases, while sports injuries explained 37% and traffic accidents 18% in 1950 to 1955.Conclusion In 2005 to 2006, we found higher rates in boys and higher overall rates compared with the 1950s but no significant differences compared with the rates in 1993 to 1994. Future studies should include patient-specific data to unravel causal factors.Level of evidence This is a Level III b study.
Keywords: children; boys; girls; epidemiology; etiology; distal forearm; fractures; trends